Too clever to see - Taylor, Kim (Belitha Press Ltd London, 2000)
Part of a series, this book reveals what is too clever to be seen, such as insects that use camouflage to disguise themselves. Through the juxtaposition of text and colour photographs which have been taken with special camera techniques the child is shown a world normally hidden from the human eye.